Digital spatial profiling identifies the tumor center as a topological niche in prostate cancer characterized by an upregulation of BAD - Huber, Ann-Kathrin; Kaczorowski, Adam; Schneider, Felix; Böning, Sarah; Görtz, Magdalena; Langhoff, David; Schwab, Constantin; Stenzinger, Albrecht; Hohenfellner, Markus; Duensing, Anette; Duensing, Stefan (Scientific reports, 2024)
Prostate cancer is characterized by a high degree of intratumoral heterogeneity. However, little is known about the spatial distribution of cancer cells with respect to specific functional characteristics and the formation of spatial niches. Here, we used digital spatial profiling (DSP) to investigate differences in protein expression in the tumor center versus the tumor periphery. Thirty-seven regions of interest were analyzed for the expression of 47 proteins, which included components of the PI3K-AKT, MAPK, and cell death signaling pathways as well as immune cell markers. A total of 1739 data points were collected from five patients. DSP identified the BCL-2 associated agonist of cell death (BAD) protein as the most significantly upregulated protein in the tumor center. BAD upregulation was confirmed by conventional immunohistochemistry, which furthermore showed a phosphorylation of BAD at serine 112 indicating its inactivation. Knockdown of BAD in prostate cancer cells in vitro led to decreased cell viability and colony growth. Clinically, high BAD expression was associated with a shorter time to biochemical recurrence in 158 mostly high-risk prostate cancer patients. Collectively, our results suggest that the tumor center is a topological niche with high BAD expression that may drive prostate cancer progression.
Gesehen am 05.09.2025